Occurrence of the regulatory nucleotides ppGpp and pppGpp following induction of the stringent response in staphylococci. - Cassels, R (1995)
The stringent response in Escherichia coli and many other organisms is regulated by the nucleotides ppGpp and pppGpp. We show here for the first time that at least six staphylococcal species also synthesize ppGpp and pppGpp upon induction of the stringent response by mupirocin. Spots corresponding to ppGpp and pppGpp on thin-layer chromatograms suggest that pppGpp is the principal regulatory nucleotide synthesized by staphylococci in response to mupirocin, rather than ppGpp as in E. coli.